Kugelberg-Welander disease - Chowdhury, Poritosh Kumar; Paik, Bishnupada; Saha, Bishnu Pada; Roy, Poritosh Kumar; Biswas, Palash (Bangladesh Medical Journal Khulna, 2015)
Spinal muscular atrophy (SMA) is a group of genetically determined disorders affecting spinal and cranial motor neurons, characterized by proximal and distal wasting, fasciculation and weakness of muscles. This patient presented with the features of slow progression of weakness and wasting of limbs, involuntary muscle twitching & without sensory impairment. No definitive treatment is yet to be discovered. SMA in adulthood is very rare. Most cases are detected in childhood and adolescence period. Sooner the diagnosis can be done, better the prognostic value. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22560 Bang Med J (Khulna) 2014; 47 : 29-31